Rancang Bangun Purwarupa Energy Harvesting menggunakan Piezoelektrik sebagai Pembangkit Energi Listrik - Kusnandar Kusnandar; Ni Ketut Hariyawati Dharmi; Aisyah Nurul Khairiyah (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The call to use clean and sustainable energy as an alternative energy source has grown rapidly over the past decade. This was triggered by the issue of increasing environmental pollution, the limited and decreasing amount of non-renewable energy and became one of the goals of the 2030 Sustainable Development Goals (SDG). According to the principle of conservation of energy, energy cannot be fully utilized, there is always some energy wasted. The technology to reuse "wasted" energy into a source of electrical energy is called energy harvesting. This paper describes the design of a prototype energy harvesting system using a floor-mounted piezoelectric that generates electrical energy when stepped on. The system prototype is composed of 16 piezoelectric arrays which are made into 4 rows and installed in parallel. The system is equipped with the LTC358 energy harvester module and the MT 3608 step-up booster module. Test results showed electrical energy was successfully in the battery. The maximum power generated by the piezoelectric array after passing through a full-wave rectifier is 3.48 W. For the same number of footsteps against the piezoelectric array, the increase in charge of the Li-Po 150 mAH battery is smaller than that of the 250 mAH type.